Evaluation of Kidney Proximal Tubule Following Immunization with Plasmodium falciparum CIDR1α-PfEMP1 Recombinant Protein in Rats - Dewi, Rosita; Sulistyaningsih, Erma; Kusuma, Irawan Fajar; Rachmania, Sheilla; Rahma, Nafisah Hani Asyifah (Majalah Kedokteran Bandung, 2025)
Malaria vaccines are continuously explored as an approach to eradicate malaria. The cysteine-rich interdomain region 1α-Plasmodium falciparum erythrocyte membrane protein 1 (CIDR1α-PfEMP1) is an antigenic protein that can bind to the endothelial protein C receptor (EPCR) and CD36, resulting in microvascular obstruction. The PfEMP1-induced antibody can induce antibodies, reducing the severity of malaria risk by impeding cytoadherence and destructing rosette formation. Preclinical safety testing is an important step of vaccine development, including safety testing of the kidney as the main excretory organ. The proximal tubule has the most mitochondria to support its main role in reabsorption and excretion, making it prone to oxidative stress caused by foreign substances. This study aimed to evaluate kidney proximal tubule cells after CIDR1α-PfEMP1 immunization in rats. This study was conducted at the Laboratory of Biology Molecular and Biotechnology, Faculty of Medicine, University of Jember. Eight rats were injected subcutaneously with 150 µg of the protein and four rats were injected with 0.9%  NaCl on days 0, 21, and 42. The rats were euthanized on day 56. The kidney histopathological slides were stained using Hematoxylin-Eosin (HE) and the necrotic proximal tubule cells were counted at five (5) visual fields (100 cells/visual fields). The average number of necrotic cells of the control and the treatment groups were 0.125±0.25 and 2.438±2.5972 while the Mann-Whitney test showed a significance value of p=0.12,  indicating no significant difference between the control and treatment groups. In conclusion, there is no change in the kidney histopathology based on the proximal tubule necrotic cell count after CIDR1α-PfEMP1 immunization in rats.